136k views
5 votes
1. Solve the following equation.(MAFS.8.EE.3.7)

5(3x + 7) + 2x = 7x – 5(–2x + 9)

User Villanux
by
4.6k points

2 Answers

3 votes

Answer:

Your answer is: No solution (There are no values of x that make the equation true.)

Explanation:

Hope this helped : )

100% Sure I am Right : )

User Klausos Klausos
by
5.7k points
5 votes

Answer:

there is no solution

Explanation:

Expand.

15x+35+2x=7x+10x-4515x+35+2x=7x+10x−45

2 Simplify 15x+35+2x15x+35+2x to 17x+3517x+35.

17x+35=7x+10x-4517x+35=7x+10x−45

3 Simplify 7x+10x-457x+10x−45 to 17x-4517x−45.

17x+35=17x-4517x+35=17x−45

4 Cancel 17x17x on both sides.

35=-4535=−45

5 Since 35=-4535=−45 is false, there is no solution.

No Solution

User Finglish
by
5.7k points